'It's Not Really a Part of Standard Practice': Institutional Silencing of Sexuality Within Australian Mental Health Settings. (February 2022) - Urry, Kristi; Chur-Hansen, Anna; Khaw, Carole
Research seeking to understand and improve sexuality-related practice in mental health settings has paid little attention to the institutional context in which clinicians' practice is embedded. Through a social constructionist lens, we used thematic analysis to examine how 22 Australian mental health clinicians implicated the wider institutional context when discussing and making sense of sexuality-related silence within their work. Interviews were part of a study exploring participants' perceptions of sexuality and sexual health in their work more generally. Broader silences that shaped and reinforced participants' perceptions and practice choices were situated in professional education; workplace cultures; and the tools, procedures and policies that directed clinical practice. We argue that sexuality-related silence in mental health settings is located in the institutional context in which clinicians learn and work, and discuss how orienting to this broader context will benefit research and interventions to improve sexuality-related practice across health settings.